(untitled) (Malaysian Management Journal, 1997)
This paper examines the international transferability of the Japanese production system to the United States (US), Korea, Taiwan, Malaysia, Thailand, and Singapore, by utilizing the "application-adaptation analytical framework". Three major factors determine particular application-adaptation hybridization characteristics in individual countries: strategic necessity of industry and company; specific attributes of the elements comprising the Japanese production system; the historical, social, and managerial environment of the host countries.